An Overview on Honey Bee Queen Rearing Methods - Farkhary, Ibrahim Farkhary (Journal of Natural Sciences – Kabul University, 2024)
One of the most significant and essential components of a bee colony is the queen, who is responsible for all genetic traits and qualities passed down to the following generation, including calmness, resistance to illnesses and environmental stresses, the ability to produce honey, and population growth. Beekeeping can be improved by selecting good generations and using ideal resources to produce queens from the selected generations. Beekeeping success depends on producing excellent queens with optimum genetic features. Thus, the customary techniques for raising queens have been reviewed in this article. These techniques include the standard grafting method as well as additional simple techniques that do not require grafting larvae. Thus, in order to develop beekeeping, focus would need to be placed on raising queens. By doing so, Afghanistan's beekeeping industry would expand and thrive, and our nation's honey production would become self-sufficient.